Ventilation of the Bay of Bengal oxygen minimum zone by the Southwest Monsoon Current - P. M. F. Sheehan; B. G. M. Webber; B. G. M. Webber; A. Sanchez-Franks; B. Y. Queste (Ocean Science)
Oxygen minimum zones (OMZs) occupy large areas of the tropical subsurface oceans and substantially alter regional biogeochemical cycles. In particular, the removal rate of bio-available nitrogen (denitrification) from the water column in OMZs is disproportionate to their size. The Bay of Bengal is one of the strongest OMZs in the global oceans; however, variable sources of oxygen prevent the onset of large-scale denitrification. The various oxygen-supply mechanisms that maintain oxygen concentrations in the OMZ above the denitrification threshold are currently unknown. Here, using a combination of multi-platform observations and model simulations, we identify an annual supply of oxygen to the Bay of Bengal in the high-salinity core of the Southwest Monsoon Current, a seasonal circulation feature that flows northward into the bay during the South Asian southwest monsoon (i.e. June–September). Oxygen concentrations within the Southwest Monsoon Current (80–100 µmol kg−1) are higher than those of waters native to the bay (i.e. <20 µmol kg−1). These high-oxygen waters spread throughout the central and western Bay of Bengal, leading to substantial spatio-temporal variability in observed oxygen concentrations. Moreover, the northward oxygen transport of the Southwest Monsoon Current is a spatially and temporally distinct event that stands out from background oxygen transport. Model results indicate that, interannually, oxygen supply to the bay varies with the strength of the Southwest Monsoon Current more closely than with its oxygen concentration. Consequently, we suggest that predictability of the annual oxygen flux is likely aided by understanding and predicting the physical forcing of the Southwest Monsoon Current. Our results demonstrate that the current, in particular its high-salinity and high-oxygen core, is a feature relevant to the processes and communities that drive denitrification within the Bay of Bengal that has heretofore not been considered.